2018
DOI: 10.1038/s41598-018-25032-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomics Reveal the Association between SPANX Proteins and Clinical Outcomes of Artificial Insemination with Donor Sperm

Abstract: Semen analysis is used for diagnosing male infertility and evaluating male fertility for more than a century. However, the semen analysis simply represents the population characteristics of sperm. It is not a comprehensive assessment of the male reproductive potential. In this study, 20 semen samples from human sperm bank with distinctive artificial insemination with donor sperm (AID) clinical outcomes were collected and analyzed using a two-dimensional differential in-gel electrophoresis (2D-DIGE); 45 differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Few studies have proposed that the use of sperm with round cells in the protein extraction process may contaminate sperm proteome. Separation of round cells and leukocytes are carried out using gradient centrifugation method and the pure fraction of the spermatozoa are used for proteomic analysis [21,[33][34][35][36][37]. Recently, Panner Selvam et al investigated the interference of round cell proteins in the proteome of sperm and their effect on biological pathways associated with sperm function [38,39].…”
Section: Proteomic Analysis Using Lc-ms/msmentioning
confidence: 99%
“…Few studies have proposed that the use of sperm with round cells in the protein extraction process may contaminate sperm proteome. Separation of round cells and leukocytes are carried out using gradient centrifugation method and the pure fraction of the spermatozoa are used for proteomic analysis [21,[33][34][35][36][37]. Recently, Panner Selvam et al investigated the interference of round cell proteins in the proteome of sperm and their effect on biological pathways associated with sperm function [38,39].…”
Section: Proteomic Analysis Using Lc-ms/msmentioning
confidence: 99%
“…Semen samples are subjected to different types of processing techniques such as single gradient centrifugation, double gradient centrifugation or multilayer gradient centrifugation to separate the spermatozoa from the seminal plasma. Several studies have used a density gradient centrifugation step to remove round cells and immature germ cells from semen samples to isolate a pure sperm fraction (Amaral, Paiva, et al., 2014; Intasqui et al., 2013; Martínez‐Heredia et al., 2006; Wang et al., 2014, 2018). Further, proteomic studies on round cells and spermatozoa revealed that the influence of round cell proteins as contaminant in the sperm proteome was insignificant or very negligible (Panner Selvam, Agarwal, Dias et al., 2019; Panner Selvam, Agarwal, Dias, Martins, & Samanta, 2019).…”
Section: Techniques In Proteomicsmentioning
confidence: 99%
“…Gradient centrifugation techniques are widely used to process the semen samples to obtain a pure population of spermatozoa. To date, some studies have used only pure cultures of sperm (without round cells) for global proteomic analysis [17,18,19,20,21], whereas others have used neat semen samples [20,22,23,24]. Thus, it is still unclear (1) whether the processing of semen samples have any interference in the sperm protein expression, and (2) what the contribution is of non-spermatogenic proteins in the evaluation of sperm proteomic profile.…”
Section: Introductionmentioning
confidence: 99%